Clinical Trials in Pakistan: Opportunities and Challenges - Irumnaz, Azizunissa; C. Nair, Satish (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2014)
Pakistan is a developing country bordering India and China. It is the seventh most populous country in the world. Though there is a large treatment naive population, high disease burden, well established and internationally recognized, Good Clinical Practice compliant health care institutions, internationally trained, English speaking researchers, yet Pakistan has not made its mark in the global clinical trials market. Even though Clinical trials have been going on for well over a decade in the country, the activities have been fragmented and efforts will need to be made to streamline the national infrastructure. The manuscript discusses the challenges and opportunities to conduct clinical trials in Pakistan.
Keywords: health infrastructure